Conditional protein degradation in Yarrowia lipolytica using the auxin-inducible degron - Han, Zhenlin; Maruwan, Jessica; Tang, Yinjie; Su, Wei Wen (Frontiers in Bioengineering and Biotechnology, 2023)
Conditional protein degradation is a powerful tool for controlled protein knockdown. The auxin-inducible degron (AID) technology uses a plant auxin to induce depletion of degron-tagged proteins, and it has been shown to be functional in several non-plant eukaryotes. In this study, we demonstrated AID-based protein knockdown in an industrially important oleaginous yeast Yarrowia lipolytica. Using the mini-IAA7 (mIAA7) degron derived from Arabidopsis IAA7, coupled with an Oryza sativa TIR1 (OsTIR1) plant auxin receptor F-box protein (expressed from the copper-inducible MT2 promoter), C-terminal degron-tagged superfolder GFP could be degraded in Y. lipolytica upon addition of copper and the synthetic auxin 1-Naphthaleneacetic acid (NAA). However, leaky degradation of the degron-tagged GFP in the absence of NAA was also noted. This NAA-independent degradation was largely eliminated by replacing the wild-type OsTIR1 and NAA with the OsTIR1(F74A) variant and the auxin derivative 5-Ad-IAA, respectively. Degradation of the degron-tagged GFP was rapid and efficient. However, western blot analysis revealed cellular proteolytic cleavage within the mIAA7 degron sequence, leading to the production of a GFP sub-population lacking an intact degron. The utility of the mIAA7/OsTIR1(F74A) system was further explored in controlled degradation of a metabolic enzyme, beta-carotene ketolase, which converts beta-carotene to canthaxanthin via echinenone. This enzyme was tagged with the mIAA7 degron and expressed in a beta-carotene producing Y. lipolytica strain that also expressed OsTIR1(F74A) controlled by the MT2 promoter. By adding copper and 5-Ad-IAA at the time of culture inoculation, canthaxanthin production was found to be reduced by about 50% on day five compared to the control culture without adding 5-Ad-IAA. This is the first report that demonstrates the efficacy of the AID system in Y. lipolytica. Further improvement of AID-based protein knockdown in Y. lipolytica may be achieved by preventing proteolytic removal of the mIAA7 degron tag.